Factors Influencing Consumer Buying Behaviour of Male Skincare Products: A Study of Mumbai Metropolitan City - Banerjee, Sanchayita; Namboodiri, Sooraj (Indian Journal of Marketing, 2018)
Purpose: The paper explored the perceptions of male consumers towards skincare products, and specific focus was given on determining the factors influencing the male buying behaviour for such products. The paper attempted to analyze if there was any significant impact of some demographic variables like age and occupation on these factors. The purpose of this study was to provide insights gained from the research regarding consumer buying behaviour and preference of male skincare products that would be helpful for the marketers in the booming metrosexual market. Design/Methodology/Approach: The paper opted for a combination of exploratory and descriptive study using a structured questionnaire consisting of 30 Likert statements rated using a 5-point scale. Data were gathered from 200 young males of Mumbai city. EFA (exploratory factor analysis) was performed to find out the influencing factors governing the male skincare market. It was further analyzed in the background of age and occupational groups to find the dominance of those factors using Kruskal - Wallis H test and post hoc Dunn's test. Findings: The results showed mixed effect of age and occupation on men's buying behavior towards skincare products related to the extracted factors. The insights gained from the study will direct marketers to develop marketing and communication strategies with a focused direction and access the market in a better manner. Research Limitations/Implications: As the study covered only one metropolitan city, it can be further extended to more cities for better generalizability. There are many other important demographic factors like income, or psychographic factors like culture and social class, which could be moderating variables influencing the male skincare buying decisions. Originality/Value: The paper identified the intrinsic motivational factors towards male skincare products and their significance on age and occupation as moderating variables.